2011
DOI: 10.1063/1.3656450
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetoimpedance and field sensitivity in microstructure controlled FeSiCuNbB ribbons

Abstract: Giant magnetoimpedance effect in ultrasoft FeAlSiBCuNb nanocomposites for sensor applications J. Appl. Phys. 98, 014316 (2005); 10.1063/1.1953864 Valve behavior of giant magnetoimpedance in field-annealed Co 70 Fe 5 Si 15 Nb 2.2 Cu 0.8 B 7 amorphous ribbon nanocomposite materials consisting of nanocrystalline phase in an amorphous matrix were obtained by heat-treatment of their precursor amorphous ribbons. The influence of structural modifications induced during the heat-treatment on soft magnetic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
1
2
1
Order By: Relevance
“…This different behavior is due to various thicknesses of the ribbons, as we have explained before. The obtained high magnetic field sensitivity of our ribbons compares favorably with the previous results reported by other groups [19,40,41], which makes them prospective materials for potential magnetic sensors applications [19,20].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 89%
“…This different behavior is due to various thicknesses of the ribbons, as we have explained before. The obtained high magnetic field sensitivity of our ribbons compares favorably with the previous results reported by other groups [19,40,41], which makes them prospective materials for potential magnetic sensors applications [19,20].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 89%
“…Particularly, the TFA ribbons can reach field sensitivities as high as 200%/(kA/m) in the field range 225-575 A/m at 3 MHz. This field-sensitivity value is larger than previous reported values in Fe systems [65,66]. In addition, in Figure 5a, it is observed that the maximum field sensitivity is reduced from 80 MHz for the as-cast sample to the frequency range of 1-5 MHz for the annealed samples.…”
Section: Magnetoimpedance Responsecontrasting
confidence: 63%
“…6.It shows that the effective inductance for the sample annealed at 550°C is highest among all annealed samples. The relative permeability dependence on the annealing temperature for FeCuNbSiB ribbons was also estimated [13]. The frequency dependence of relative permeability ∆µ'/µ'=µ'(90 Oe)-µ'(0)]/µ'(90 Oe) for Fe 73.5 Cu 1 Nb 2 VSi 13.5 B 9 annealed at 550°C is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%